Biomarkers in Amyloid-β Immunotherapy Trials in Alzheimer's Disease - Blennow, Kaj (Nature Publishing Group, 2014)
Drug candidates directed against amyloid-β (Aβ) are mainstream in Alzheimer's disease (AD) drug development. Active and passive Aβ immunotherapy is the principle that has come furthest, both in number and in stage of clinical trials. However, an increasing number of reports on major difficulties in identifying any clinical benefit in phase II–III clinical trials on this type of anti-Aβ drug candidates have caused concern among researchers, pharmaceutical companies, and other stakeholders. This has provided critics of the amyloid cascade hypothesis with fire for their arguments that Aβ deposition may merely be a bystander, and not the cause, of the disease or that the amyloid hypothesis may only be valid for the familial form of AD. On the other hand, most researchers argue that it is the trial design that will need refinement to allow for identifying a positive clinical effect of anti-Aβ drugs. A consensus in the field is that future trials need to be performed in an earlier stage of the disease and that biomarkers are essential to guide and facilitate drug development. In this context, it is reassuring that, in contrast to most brain disorders, research advances in the AD field have led to both imaging (magnetic resonance imaging (MRI) and PET) and cerebrospinal fluid (CSF) biomarkers for the central pathogenic processes of the disease. AD biomarkers will have a central role in future clinical trials to enable early diagnosis, and Aβ biomarkers (CSF Aβ42 and amyloid PET) may be essential to allow for testing a drug on patients with evidence of brain Aβ pathology. Pharmacodynamic Aβ and amyloid precursor protein biomarkers will be of use to verify target engagement of a drug candidate in humans, thereby bridging the gap between mechanistic data from transgenic AD models (that may not be relevant to the neuropathology of human AD) and large and expensive phase III trials. Last, downstream biomarker evidence (CSF tau proteins and MRI volumetry) that the drug ameliorates neurodegeneration will, together with beneficial clinical effects on cognition and functioning, be essential for labeling an anti-Aβ drug as disease modifying.